Reduced cerebral oxygen–carbohydrate index during endotracheal intubation in vascular surgical patients. (5th June 2014) - Fabricius‐Bjerre, Andreas; Overgaard, Anders; Winther‐Olesen, Marie; Lönn, Lars; Secher, Niels H.; Nielsen, Henning B.
Summary Brain activation reduces balance between cerebral consumption of oxygen versus carbohydrate as expressed by the so‐called cerebral oxygen‐carbohydrate‐index (OCI). We evaluated whether preparation for surgery, anaesthesia including tracheal intubation and surgery affect OCI. In patients undergoing aortic surgery, arterial to internal jugular venous (a‐v) concentration differences for oxygen versus lactate and glucose were determined from before anaesthesia to when the patient left the recovery room. Intravenous anaesthesia was supplemented with thoracic epidural anaesthesia for open aortic surgery (n = 5) and infiltration with bupivacaine for endovascular procedures (n = 14). The a‐v difference for O2 decreased throughout anaesthesia and in the recovery room (1·6 ± 1·9 versus 3·2 ± 0·8 mmol l−1, mean ± SD), and while a‐v glucose decreased during surgery and into the recovery (0·4 ± 0·2 versus 0·7 ± 0·2 mmol l−1, P<0·05), a‐v lactate did not change significantly (0·03 ± 0·16 versus −0·03 ± 0·09 mmol l−1). Thus, OCI decreased from 5·2 ± 1·8 before induction of anaesthesia to 3·2 ± 1·0 following tracheal intubation (P<0·05) because of the decrease in a‐v O2 with a recovery for OCI to 4·6 ± 1·4 during surgery and to 5·6 ± 1·7 in the recovery room. In conclusion, preparation for surgery and tracheal intubation decrease OCI that recovers during surgery under the influence of sensory blockade.